Ecolinguistic dynamics of English loanwords in Chinese: a case study on terms for cement - Ruifeng Mo; Hao-Zhang Xiao (Humanities & Social Sciences Communications)
Abstract Ecolinguistics explores the interplay between language and the environment, offering insights into how linguistic elements adapt and evolve. This study examines five cement-related English loanwords in Chinese to uncover the evolutionary mechanisms governing the adaptation of these loanwords by analyzing their ecological dynamics. The research quantitatively evaluates the ecology of these loanwords using two indicators: lexical niche breadth and overlap. The results are as follows: (1) The emergence of English loanwords in Chinese is intricately linked to specific social environments. As new concepts and items are introduced from abroad, the masses initially coin new loanwords, which are later standardized by authoritative bodies. (2) The vitality of the loanwords correlates with their niche breadth. The competition among lexical variants is influenced by niche overlap. The loanwords for cement are ranked by vitality values in descending order—ShuiNi (水泥/water mud): 3.221, YangHui (洋灰/foreign ash): 2.350, ShuiMenTing (水门汀/water-gate concrete): 1.385, HongMaoNi (红毛泥/red-hair clay): 1.202, and ShiMinTu (士敏土/sticky soil): 0.879. (3) The endangerment of the loanwords results from the synergistic interaction between external (nature, society, culture, psychology) and internal (sound, form, meaning, grammar) environments. Intense competition arises due to multiple synonyms for the same entity, and adaptation challenges occur when the loanwords do not precisely fit the entity. Among the five loanwords for cement, the first two exhibit higher vitality and continue to develop sustainably, while the last three show lower vitality and are gradually becoming endangered. As these loanwords undergo continuous evolution, a lexical ecocontinuum emerges: (i) extinct in the wild—ShiMinTu; (ii) critically endangered—HongMaoNi; (iii) endangered—ShuiMenTing; (iv) vulnerable—YangHui; (v) least concerned—ShuiNi.